PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK BERBASIS WORDWALL PADA TEMA 7 PERISTIWA DALAM KEHIDUPAN - Siahaan, Daud Hamonangan; Lina Novita; Resyi A Gani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Development of Wordwall-Based Electronic Student Worksheets on Theme 7 Events in Life Learning 1. This research is a Research and Development (R&D) research using the ADDIE research method (Analysis, Design, Development, Implementation, Evaluation). The subjects involved in this study were 2 (two) Pakuan University lecturers as media experts and linguists, and also 1 (one) BPK PENABUR Bogor Elementary teacher as material experts, as well as students in class V (five) at BPK PENABUR Bogor Elementary School. Media experts gave a validation score to the Wordwall of 96% with very good qualifications, linguists gave a validation score to the Wordwall of 100% with very good qualifications, material experts gave a validation score to Wordwall-based E-LKPD application Wordwall 96% with very good qualifications, and based on field trials on students in grade V (five) getting a score of 90% with very good qualifications. Thus it can be concluded and stated that the Wordwall is stated to be very valid and is feasible to be tested on fifth-grade students and applied to theme 7 sub-theme 2 learning 1 and used by the teacher.